HUBUNGAN ANTARA KEGIATAN EKSTRAKURIKULER DENGAN KEAKTIFAN SISWA DALAM BERDISKUSI DI SEKOLAH MENENGAH PERTAMA MUHAMMADIYAH 4 PALEMBANG - Nurrahman Nurrahman; Fitri Oviyanti; Syarnubi Syarnubi (PAI RAFAH, 2021)
Extracurricular activities are a series of additional activities carried out outside of class hours with the aim of enriching and expanding the potential aspects of the interests, talents and abilities of students held by the school in accordance with the school regulations. Discussion is a discussion of a topic with a view to formulating a common interest and the purpose of this activity is to find a solution to the problem discussed. The purpose of this study was to obtain data on the relationship between extracurricular activities and student activity in discussions at SMP Muhammadiyah 4 Palembang.This type of research used in this research is quantitative (non-experimental) research using simple statistical analysis techniques using the percentage formula and product moment technique. The sample used in this study was class VIII totaling 177 students taken by random sampling technique, the sample amounted to 36 students. To obtain data the author uses the method of observation, questionnaires, and documentation.Based on the results of the analysis of research data, the correlation value calculation shows the number rxy = 0.95, this means that there is a positive relationship (unidirectional) between extracurricular activities with student activity in discussion. Viewed from the level of 1% = 0.4238 and the level of 5% = 0.3291 means that the table> r then the consequence is (Ha) is accepted (Ho) is rejected. And it can be concluded that the correlation value of 0.95 obtained is not negative, because it is in the range of the relationship between 0.40-0.70 on the interpretation of the value of 'r' product moment, it can be known that the variable X and Y are very strong, from the analysis these data, thus the proposed hypothesis is accepted, and there is a significant or very strong relationship between the two variables X and Y variables.